The secret service of tea and treason eaudiobook - Holton, India (Dangerous Damsels, 2023)
An International Bestseller! One of... Library Journal's Best Romances of the Year Amazon's Best Romances of April Buzzfeed's Romance Books To Look Out For In 2023 Two rival spies must brave pirates, witches, and fake matrimony to save the Queen. Known as Agent A, Alice is the top operative within the Agency of Undercover Note Takers, a secret government intelligence group that is fortunately better at espionage than at naming itself. From managing deceptive witches to bored aristocratic ladies, nothing is beyond Alice’s capabilities. She has a steely composure and a plan always up her sleeve (alongside a dagger and an embroidered handkerchief). So when rumors of an assassination plot begin to circulate, she’s immediately assigned to the case.  But she’s not working alone. Daniel Bixby, otherwise known as Agent B and Alice's greatest rival, is given the most challenging undercover assignment of his life— pretending to be Alice’s husband. Together they will assume the identity of a married couple, infiltrate a pirate house party, and foil their unpatriotic plans.  Determined to remain consummate professionals, Alice and Daniel must ignore the growing attraction between them, especially since acting on it might prove more dangerous than their target.